Investigating English writing problems among high achiever Post-UPSR learners in Sabah - Dg Nursazwani Daud; Wardatul Akmam Din; Noraini Said; Suyansah Swanto (Global Academic Excellence, 2021)
The purpose of the study was to investigate the writing problems faced by the Post-UPSR learners during their primary school years. The data was obtained from 217 high achiever learners who scored an A on the UPSR. These learners, who had completed primary schools and taken the UPSR exam, are now enrolled in secondary schools as Form 1 learners. The method used is a quantitative study. A questionnaire was used as the instrument in the study. The analysis of the study uses SPSS which involves frequency and percentage. The data revealed that Malaysian ESL primary school learners struggle with writing tasks, particularly due to insufficient of vocabulary knowledge. The findings of the study will be valuable to ESL researchers and educators in assisting learners with their writing difficulties. Teachers or researchers can develop appropriate solutions to the issues once the writing issue has been identified.